THE APLICATION OF DISCOVERY LEARNING MODEL IN PKN TO IMPROVING THE STUDENT CREATIVE THINKING - Syaifullah, Ghina Aisyah Endang Sumantri (Department of Civic Education, 2016)
This study in the background backs after seeing class IX-J at SMPN 1 Cicalengka, which is still a lack of creative thinking abilities of students in the class, demonstrated by at least courage learners in conveying new ideas, because students often follow the idea of learners who are considered more intelligent, and teachers often use the lecture method of teaching. The method used in this research is a classroom action research. instruments used were interviews, observations, questionnaires, field notes, and documentation, while the findings of this research are: 1) Planning learning civics by using a model of discovery learning is to prepare lesson plans, and grouping learners 2) Implementation of learning civics by using a model of discovery learning to do as much three cycles, where teachers prepare the cases related to the material, then the teacher gives time for each group to perform analysis on the case, and each group presents alternative answers and ideas of the ideas of the group 3) Excellence model of discoery learning can enhance the creative thinking of learners 4 ) constraints experienced is the time required to implement the model discoery learning quite a lot, 5) the efforts that optimize the role of the teacher as a facilitator in the learning process.Key words: Model Discovery Learning, Creative Thinking, Civics Education.